Computer simulation of a pH-responsive drug delivery system formed by μ-ABC miktoarm star polymers in aqueous solution - Zengwei Ma; Lijun Li; Nan Hu; Jianwei Wei; Lin Chen (International Journal of Smart and Nano Materials)
The development of pH-responsive drug delivery systems is a critical frontier in the field of targeted cancer therapy. This study presents a comprehensive investigation into the self-assembly and drug release behavior of a pH-responsive anticancer drug delivery system utilizing μ-ABC miktoarm star polymers through dissipative particle dynamics (DPD) simulations. By changing the hydrophilic arm length, the morphology of drug carriers can manifest as vesicles, ellipsoidal micelles, or spherical micelles. The length of the pH-responsive arm is crucial in influencing the size and aggregation number of the carriers, especially when the hydrophilic arms are long. At low pH values, when the pH-responsive arm is fully protonated, drug-loaded vesicles undergo a transformation into long nanoribbons, whereas ellipsoidal and spherical micelles disassemble into smaller fragments. Among these structures, spherical drug-loaded micelles exhibit superior performance concerning drug release rate and uniformity. Furthermore, the drug release mechanisms at different pH values for the three types of drug carriers have also been studied in detail. Notably, we find that the electrostatic interaction is a critical factor in determining the drug release mechanism. This research provides valuable insights into the design of pH-responsive drug carriers based on the miktoarm star polymers.